The Corrective Effect of Ideological and Moral Education on the Negative Psychology of Girl Students in Physical Education - Lin Yao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The research objective was to check the corrective effect of ideological and moral education on the negative psychology of female students in physical education. The study involved three groups of female students: a regular teaching group, a 6-week exercise group, and a 12-week exercise group. The exercise intervention plan included secondary public aerobics, with controlled exercise intensity through heart rate indicators. The results of the study revealed that, before the experiment, there were no significant differences in the inhibitory function, conversion function, and refresh function components among the groups, indicating homogeneity. However, after the exercise interventions, significant improvements were observed in the inhibitory function in both the 6-week and 12-week exercise groups compared to the regular teaching group. Similarly, the 12-week exercise group showed a significant improvement in conversion function compared to the conventional teaching group. Moreover, the refresh function also exhibited significant improvement in the 12-week exercise group compared to the conventional teaching group. The findings suggest that continuous physical exercise, with moderate intensity lasting for 12 weeks, coupled with ideological and moral education, can be beneficial in enhancing psychological regulation functions among female college students. These results hold practical implications for incorporating targeted exercise interventions and educational approaches in physical education to promote students' psychological well-being. However, future research with more diverse samples and longer-term interventions is warranted to further validate and extend these findings because future research could be explored to other countries.